2012
DOI: 10.1124/jpet.111.190710
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibition Reduces Proliferation, Collagen Expression, and Inflammatory Cytokine Production in Nasal Mucosa and Polyp Fibroblasts

Abstract: Proteasome inhibitors, used in cancer treatment for their proapoptotic effects, have anti-inflammatory and antifibrotic effects on animal models of various inflammatory and fibrotic diseases. Their effects in cells from patients affected by either inflammatory or fibrotic diseases have been poorly investigated. Nasal polyposis is a chronic inflammatory disease of the sinus mucosa characterized by tissue inflammation and remodeling. We tested the hypothesis that proteasome inhibition of nasal polyp fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…Thirty to 50% confluent nasal fibroblasts were transfected with 20 nM of either MKP-1 or GILZ Silencer Select pre-designed siRNA or Silencer Select negative control siRNA using lipofectamine RNAiMAX, as previously reported [ 29 ]. Twenty-four hours after transfection, cells were pre-incubated in the absence or presence of LPS (10 μg/ml) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty to 50% confluent nasal fibroblasts were transfected with 20 nM of either MKP-1 or GILZ Silencer Select pre-designed siRNA or Silencer Select negative control siRNA using lipofectamine RNAiMAX, as previously reported [ 29 ]. Twenty-four hours after transfection, cells were pre-incubated in the absence or presence of LPS (10 μg/ml) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated and reverse transcribed to cDNA [ 29 ]. GRα , GRβ , MKP-1 , GILZ , and RNA polymerase II (RPII) mRNA expression was analyzed by real-time PCR using TaqMan Fast Universal PCR Master Mix and either customized (for GRα ) or predesigned (for all other genes) TaqMan Gene Expression Assays (Life Technologies) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that p21 accumulation in UUO kidneys is moderately enhanced by Skp2 deficiency [20]. In addition, the accumulation of p21 and p27 as a result of proteasome inhibition is associated with inhibition of interstitial fibroblast proliferation [92]. Therefore, p21 and p27 are negative regulators of interstitial cell proliferation while upregulated Skp2 in the UUO kidney enhances their degradation to promote interstitial fibroblast proliferation and myofibroblast formation as critical stages in the EMT.…”
Section: Role Of the Skp2/p27 Axis In The Progression Of Renal Damagementioning
confidence: 99%
“…In these cell lines, treatment with a proteasome inhibitor suppressed fibrosis together with reduced MCP-1 production and TGF-β- and TNF-α-induced collagen mRNA expression. Moreover, the inflammatory response in fibroblasts is inhibited by suppression of IL-1β-/TNF-α-induced NF-κB activation and IL-1β-induced IL-6/8 production [92]. These results suggest that the accumulated p21 and p27 in fibroblasts can inhibit tissue inflammation and progressive fibrosis.…”
Section: Role Of the Skp2/p27 Axis In The Progression Of Renal Damagementioning
confidence: 99%
See 1 more Smart Citation